Contemporary movement of the Earth's crust in the Northwestern Vietnam by continuous GPS data - Minh, Le Huy; Hung, Vu Tuan; Hu, Jyr- Ching; Minh, Nguyen Le; Huang, Bor- Shouh; Chen, Horng- Yue; Thang, Nguyen Chien; Thanh, Nguyen Ha; Thanh, Le Truong; Mai, Nguyen Thi; Hong, Pham Thi Thu (Vietnam Journal of Earth Sciences, 2020)
The paper presents an estimation of the Earth’s crustal motion from the continuous GPS data at 6 stations (MTEV, MLAY, DBIV, TGIV, SMAV and SLAV) in the Northwestern and at PHUT (Hanoi) station using GAMIT/GLOBK software. The absolute displacements of the Earth’s crust at 7 stations in the IGS14 frame are respectively: 34.10±0.71 mm/yr (DBIV), 34.31±0.65 mm/yr (PHUT), 34.51±0.75 mm/yr (SMAV), 34.55±0.80 mm/yr (MLAY), 34.80±0.72 mm/yr (TGIV), 34.93±0.99 mm/yr (SLAV) and 35.59±0.73 mm/yr (MTEV), in the southeastward with the azimuth range 104-108o.  The Son La fault is a right-lateral slip fault with a shear amplitude of ~1.5 mm/yr. The Lai Chau-Dien Bien fault is a left-lateral slip fault with a shear amplitude of ~1.9 mm/yr. Although the absolute velocities at the DBIV, SMAV, SLAV, TGIV and MLAY stations are evaluated with the error <1 mm/yr, the relative displacement on the Ma River fault is of ~0.5 mm/yr, and it seems that we still do not have a reliable assessment of the slip rate on the Ma River right-lateral slip fault.